2022
DOI: 10.1039/d1en00713k
|View full text |Cite
|
Sign up to set email alerts
|

Particle size determines the accumulation of platinum nanoparticles in the estuarine amphipod, Leptocheirus plumulosus

Abstract: Determination of size-dependent accumulation of platinum nanoparticles using single particle-inductively coupled plasma-mass spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…In case of filter feeders, NOM could effectively filter particles with sizes within a certain range, such as Daphnia magna, which typically ingests particles within the size range of 0.5-40 μm (Demott 1982). Sikder et al reported that, with the increased size of Pt NMs, the uptake rate of Pt NMs increased, whereas the elimination rate decreased by amphipods (Sikder et al 2021). Lu et al…”
Section: Mechanisms By Which Nom Influences the Uptake Of Nms By Aqua...mentioning
confidence: 99%
“…In case of filter feeders, NOM could effectively filter particles with sizes within a certain range, such as Daphnia magna, which typically ingests particles within the size range of 0.5-40 μm (Demott 1982). Sikder et al reported that, with the increased size of Pt NMs, the uptake rate of Pt NMs increased, whereas the elimination rate decreased by amphipods (Sikder et al 2021). Lu et al…”
Section: Mechanisms By Which Nom Influences the Uptake Of Nms By Aqua...mentioning
confidence: 99%
“…As a result, an ecotoxicological assessment of these particles is required prior to their extensive use in agricultural ecosystems. Ecotoxicological studies have shown that AgNPs and Ag ions may have a deleterious influence on aquatic species, such as Daphnia magna , Pseudokirchneriella subcapitata , Lemna minor , and Danio rerio ( Hlavkova et al., 2019 ; Sikder et al., 2022 ). Though, in contrast to freshwater and marine organism, the potential harm of AgNPs in soils has been insufficiently explored.…”
Section: Introductionmentioning
confidence: 99%